THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL COMMITMENT, AND JOB SATISFACTION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (STUDY AT ST CAROLUS HOSPITAL JAKARTA) - Rama Kelana, Robertus; Tajuddin Pogo (Dinasti International Journal of Management Science, 2022)
The research which was written with "The Influence of Transformational Leadership, Organizational Commitment, and Job Title on Organizational Citizenship Behavior (OCB)" aims to determine directly the partial and simultaneous or joint effect of the independent variables, namely the Transformational Leadership variable, the Organizational Commitment variable, and Working variables on Organizational Citizenship Behavior (OCB) variables, the research conducted by this researcher also aims to determine which independent variables have the most influence on Organizational Citizenship Behavior (OCB) variables. working to serve the health services of St.Carolus Hospital Jakarta. The analytical method used by the researcher is the multiple linear regression analysis method which is processed with the help of the SPSS program, the results carried out by this researcher show the results that partially there is no significant positive effect on the variables of Transformational Leadership and Organizational Commitment to Organizational Citizenship Behavior (OCB )and Partially, this study shows a significant positive effect between job satisfaction variables on Organizational Citizenship Behavior (OCB) on doctors who work at St. Carolus Hospital, Jakarta.